Colloidal Quantum Dot Light-Emitting Diodes Employing Phosphorescent Small Organic Molecules as Efficient Exciton Harvesters - Mutlugun, Evren (2016)
Nonradiative energy transfer (NRET) is an alternative excitation mechanism in colloidal quantum dot (QD) based electroluminescent devices (QLEDs). Here, we develop hybrid highly spectrally pure QLEDs that facilitate energy transfer pumping via NRET from a phosphorescent small organic molecule-codoped charge transport layer to the adjacent QDs. A partially codoped exciton funnelling electron transport layer is proposed and optimized for enhanced QLED performance while exhibiting very high color purity of 99%. These energy transfer pumped hybrid QLEDs demonstrate a 6-fold enhancement factor in the external quantum efficiency over the conventional QLED structure, in which energy transfer pumping is intrinsically weak.